Muslim converts in Malaysia: the problem of cultural adjustment - Abdullah @ Chuah Hock Leng, Osman; Muhamad Shukri, Abdul Salam (IIUM Press, 2008)
This book is a part of a study into the social interaction and integration of Muslim converts with Malay Muslims and also non-Muslim Chinese, Indians and others in Malaysia and the changes the converts go through in relating to the cultural norms of their own ethnic groups. After having embraced Islam, there could be new adjustments of culture, customs, and ways of living. The task of this study is to evaluate these changes in the context of the backgrounds of converts in Malaysia.